Comparação de modalidades de enxertia na propagação da mangueira (Mangifera indica L.) - V R Pinheiro, Rubens; Andersen, Otto; Fortes, José Maurício (Revista Ceres, 2025)
A study was made to determine which method of grafting, applied to the mango, would produce best results. The cultivar ’Ubá’ was used as scion, and some commom varieties fromthe region were employed as stock.